The Effect of Wi-Fi Radiation on Human Body - Naeemah, Yasameen Sabbar (American Journal of Bioscience and Clinical Integrity, 2025)
Background: Wi-Fi (Wireless Fidelity) technology has become an essential part of current life that permitting wireless internet connectivity in homes, schools, public spaces and workplaces that which enabling communication and internet access. Wi-Fi transmits data using radiofrequency of electromagnetic radiation (EMR) that consider a type of radiation (non-ionizing) meaning they absence an energy to directly destroy DNA. In recent years, as worldwide requirement on wireless communication raises particularly among youths and children, therefore daily life has raised worries about their potential health effects of exposure for these Wi-Fi radiation, especially given the nearness of devices to the human body. So the hazard health on human of Wi-Fi by the electromagnetic radiation of its. However, this radiation emit may contribute to various health problems, for example heart disease, sleep disorders, brain tumors, hearing issues, and human infertility, all these happened when exposure for long time. Also the Wi-Fi radiation have potential effects on brain activity, sleep patterns, fertility, oxidative stress levels, and overall cellular function. However, existing research remains questionable and often inconsistent, with some studies reporting physiological changes while others observe no measurable effects, this different in idea may below to the long of exposure time. Amis: This review aims to study the harmful effects of electromagnetic radiation (EMR) as of Wi-Fi on human health and suggest directions for future investigation.